Occurrence and environmental impact of industrial agglomeration on regional soil heavy metalloid accumulation: A case study of the Zhengzhou Economic and Technological Development Zone (ZETZ), China. (1st February 2020) - Chen, Yinan; Ma, Jianhua; Miao, Changhong; Ruan, Xinling
Abstract: To clarify whether industrial agglomeration affects soil heavy metalloid (HM) accumulation and pollution and whether industrial agglomeration results in less soil HM pollution than in areas without industrial agglomeration, an investigation of the HM concentration and pollution in soils in an industrial agglomeration area, the national Zhengzhou Economic and Technological Development Zone (ZETZ), was conducted. Determinations of the Hg, Pb, Cr, As, Zn, Cd, Ni, Co, Cu and Mn concentrations in soils were performed using inductively coupled plasma-mass spectrometry, inductively coupled plasma-atomic emission spectrometry and atomic fluorescence spectrometry (ICP-MS, ICP-AES). The contamination factor ( CF ) of different elements, and the comprehensive pollution load index ( PLI ) of multiple HMs were calculated. Furthermore, to quantify the relationships between industrial output and soil HM accumulation, the concept of the toxic equivalent mass of soil HM accumulation per capital output ( TEM ) is proposed. The key results are as follows: (1) The average concentrations for all the studied HMs were higher than the local background concentration (BC) values. The distribution of the soil HM concentrations showed significant spatial heterogeneity, and the regions with the highest soil HM concentrations were generally affected by local industrial activities. (2) The pollution load index ( PLI ) values indicate that the extent of the human impacts on the soil environment in the study area correspond to the slight pollution level as a whole. (3) The PLI values, the total accumulated mass of soil HMs over time per million industrial capital output ( PM t ), and the TEM values for the ZETZ, Kaifeng Carbon Factory (KCF), and Wanyang Lead Smelter (WLS) were subjected to comparative analyses, with the KCF and WLS showing markedly higher levels than the ZETZ. Accordingly, although slight HM accumulation occurred in the soil of the ZETZ, the industry-related accumulation of soil HMs in the ZETZ is significantly less than that in the KCF and WLS; thus, industrial agglomeration may be effective for reducing the intensity of HM accumulation. Highlights: Spatial patterns of heavy metalloid (HM) concentration and contamination in soils were identified. The relationships between industrial output value and soil HM accumulation were quantified. Comparative analysis the accumulation of soil HMs in an industrial agglomeration area and non-agglomeration areas.